Revealing the Concept of Aging in Turkish Nursing Students: An Exploratory Metaphor Analysis - Yilmaz, Emel Bahadir; Yüksel, Arzu (Magyar Gerontológia, 2021)
Purpose: This study aimed to reveal the perceptions of nursing students about the concept of aging through metaphors. Methods: The study was carried out in a qualitative research design. The study sample consisted of 104 senior nursing students at Aksaray University in the 2021-2022 academic year. In the study, "Metaphoric Perceptions Data Collection Form", which was prepared by the researchers in line with the literature, was used as a data collection tool. In order to collect the data, each student was asked to fill in the blanks of the sentence: "Aging is like … because …" . The analysis of the data was carried out in five stages: (1) Coding and sorting phase, (2) Sample metaphor image compilation phase, (3) Main theme and sub-themes development phase, (4) The stage of ensuring validity and reliability, and (5) Transferring the data to the computer environment. Results: Students produced a total of 102 valid metaphors for the concept of aging. The metaphors revealed the students’ perceptions of the concept of aging, and four main themes and 11 sub-themes were collected. The main themes were aging as an ending story, as a need for care, attention, and support, as a new beginning, and as a source of life. Sub-themes were acceptance, no turning back, approaching the end, deprivation, helplessness, being dependent, rooting, starting, guiding, being a building block, and being valued. Conclusion: Nursing students’ metaphors about aging are generally negative, but also contain expressions of respect.